0D/2D Heterostructures Vertical Single Electron Transistor. (4th December 2020) - Mouafo, Louis Donald Notemgnou; Godel, Florian; Simon, Laurent; Dappe, Yannick J.; Baaziz, Walid; Noumbé, Ulrich Nguétchuissi; Lorchat, Etienne; Martin, Marie‐Blandine; Berciaud, Stéphane; Doudin, Bernard; Ersen, Ovidiu; Dlubak, Bruno; et al.
Abstract: Mixed‐dimensional heterostructures formed by the stacking of 2D materials with nanostructures of distinct dimensionality constitute a new class of nanomaterials that offers multifunctionality that goes beyond those of single dimensional systems. An unexplored architecture of single electron transistor (SET) is developed that employs heterostructures made of nanoclusters (0D) grown on a 2D molybdenum disulfide (MoS2 ) channel. Combining the large Coulomb energy of the nanoclusters with the electronic capabilities of the 2D layer, the concept of 0D–2D vertical SET is unveiled. The MoS2 underneath serves both as a charge tunable channel interconnecting the electrode, and as bottom electrode for each v‐SET cell. In addition, its atomic thickness makes it thinner than the Debye screening length, providing electric field transparency functionality that allows for an efficient electric back gate control of the nanoclusters charge state. The Coulomb diamond pattern characteristics of SET are reported, with specific doping dependent nonlinear features arising from the 0D/2D geometry that are elucidated by theoretical modeling. These results hold promise for multifunctional single electron device taking advantage of the versatility of the 2D materials library, with as example envisioned spintronics applications while coupling quantum dots to magnetic 2D material, or to ferroelectric layers for neuromorphic devices. Abstract : The concept of 0D–2D vertical single electron transistors is unveiled. It allows to combine the large Coulomb energy of nanoclusters with the electronic capabilities of a two‐dimensional channel, acting both as the bottom electrode and dielectric for gate control of the nanoclusters charge states. These findings open doors to unexplored architectures of multifunctional quantum devices based on mixed‐dimensional heterostructures.